2017
DOI: 10.1007/s10903-017-0602-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Sodium Intake of Korean Americans with Type 2 Diabetes

Abstract: The increasing prevalence of type 2 diabetes mellitus (T2DM) and its complications including cardiovascular disease and chronic kidney disease threaten Korean Americans (KAs). High dietary sodium intake contributes to both conditions. The purpose of the study was to assess dietary sodium consumption and to examine the predictors of sodium intake among KA with T2DM. A total 232 KA who had uncontrolled diabetes participated in this study. The majority of the sample (69%) consumed more sodium than current nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 43 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Some studies reported that older age was associated with higher sodium consumption in CKD and healthy populations (Meuleman et al, 2018;Reyhani et al, 2020), while some found no association between age and sodium intake in a hypertensive population (Wicaksana et al, 2021). Some previous studies found an influence of gender on SCB in healthy, hypertensive, and type 2 diabetes populations (Aziz et al, 2021;Ko et al, 2018;Reyhani et al, 2020), whereas others found no association in nondialysis CKD and heart failure patients (Meuleman et al, 2018;Smith et al, 2019). Mestral et al (2017) conducted a systematic review and reported that individuals with low socioeconomic status had excessive sodium consumption.…”
mentioning
confidence: 99%
“…Some studies reported that older age was associated with higher sodium consumption in CKD and healthy populations (Meuleman et al, 2018;Reyhani et al, 2020), while some found no association between age and sodium intake in a hypertensive population (Wicaksana et al, 2021). Some previous studies found an influence of gender on SCB in healthy, hypertensive, and type 2 diabetes populations (Aziz et al, 2021;Ko et al, 2018;Reyhani et al, 2020), whereas others found no association in nondialysis CKD and heart failure patients (Meuleman et al, 2018;Smith et al, 2019). Mestral et al (2017) conducted a systematic review and reported that individuals with low socioeconomic status had excessive sodium consumption.…”
mentioning
confidence: 99%